SURVEI MINAT DAN SISTEM PENGELOLAAN MANAJEMEN SUPORTER SEPAK BOLA (BRALING MANIA) PURBALINGGA TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this research is to find out how much interest a member of the football supporters Braling Mania and find out about the description of the management management system which includes the planning, organizing, drafting, briefing and surveillance personnel history of football Braling Mania Purbalingga. The approach used in this study is a qualitative approach and use quantitative as well. Research methods used include observation, interviewing, documentation, and questionnaires. The results of this research are Interest supporters of football Mania is quite high with Braling Mania percentage 72% with some indicators that include a feeling of love, attention, attraction, engagement. Process management in supporters Braling Mania is already well underway, in terms of planning already underway in accordance with the objectives of supporters Braling Mania.